Instructional Impact of Hybrid Learning in Mathematics - Turtoga, Flordelis (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the instructional impact of hybrid learning on the mathematics performance of graduating Bachelor of Science in Information Systems (BSIS) students at Talibon Polytechnic College. Guided by blended learning theory, constructivist learning theory, cognitive load theory, the Community of Inquiry framework, self-regulated learning theory, and transactional distance theory, the research explored how hybrid learning influences academic performance, competency attainment, instructional strategies, availability of learning materials, assessment practices, and institutional support. A convergent embedded quantitative research design integrating quantitative and qualitative approaches was employed. Data were collected using survey questionnaires adapted from Albert Lagrimas (2022), semi-structured interviews, and analysis of students’ academic records. Respondents included graduating BSIS students and a mathematics instructor who had experienced the hybrid learning system implemented at the institution. Quantitative data were analyzed using descriptive and inferential statistics, while qualitative data were examined through thematic analysis and triangulation. Results indicated that students demonstrated stronger performance in Statistics and Quantitative Methods, while Mathematics II showed lower performance due to the complexity of conceptual topics and limited face-to-face interaction. Students generally reported very positive experiences with hybrid learning, particularly in competency attainment, availability of learning materials, instructional strategies, assessment practices, and institutional support. However, challenges were identified in student engagement during synchronous sessions, understanding complex online materials, timely feedback in assessments, and access to counseling support. Overall, the study concludes that hybrid learning can effectively support mathematics education when supported by appropriate instructional strategies, accessible learning resources, and comprehensive academic support systems. The findings are relevant to Sustainable Development Goal 4 (Quality Education) by promoting innovative teaching practices that improve access and quality in higher education, and SDG 9 (Industry, Innovation and Infrastructure) by encouraging the integration of digital technologies in education. The study contributes to educational and socio-technological sustainability by providing evidence-based insights for improving hybrid learning systems and strengthening institutional capacity for technology-enabled instruction in higher education.